Respuesta :

gmany

Step-by-step explanation:

Convert the equation to the slope-intercept form (y = mx + b):

[tex]-5x-3y=-7[/tex]              add 5x to both sides

[tex]-3y=5x-7[/tex]              divide both sides by (-3)

[tex]y=-\dfrac{5}{3}x+\dfrac{7}{3}[/tex]

Choose any three values of x ​​and calculate the values od y:

for x = -1:

[tex]y=-\dfrac{5}{3}(-1)+\dfrac{7}{3}=\dfrac{5}{3}+\dfrac{7}{3}=\dfrac{12}{3}=4\to(-1,\ 4)[/tex]

for x = 2:

[tex]y=-\dfrac{5}{3}(2)+\dfrac{7}{3}=-\dfrac{10}{3}+\dfrac{7}{3}=-\dfrac{3}{3}=-1\to(2,\ -1)[/tex]

for x = 5

[tex]y=-\dfrac{5}{3}(5)+\dfrac{7}{3}=-\dfrac{25}{3}+\dfrac{7}{3}=-\dfrac{18}{3}=-6\to(5,\ -6)[/tex]

Ver imagen gmany